ProTecME / Rosuzeita Fauzi ... [et al.] - Fauzi, Rosuzeita; Ahmad Sharoni, Siti Khuzaimah; Abu Bakar, Syazwan Firdaus; Isa, Roslinda; Isa, Siti Nor Ismalina; Mohd Nazeri, Diana Tasha (2021)
Workplace violence (WPV) and other forms of aggression in any setting, particularly in the workplace are unacceptable and are of serious concern. WPV can come from a variety of sources in hospitals, including patients, their families and friends, other individuals outside the hospital, and individuals who are or have been employed by the hospital. The ProTecME mobile phone app was developed specifically to fix this concern. Through its easy user interface and mechanism for efficiently reporting WPV, this is the first application in Malaysia to provide true transparency and a sense of security. The benefits of using this system can improve the rapid communication process between the victim and the management, definite documentation accountability, legal protection and reduce any possible errors. This mobile apps Prototype was given to the stakeholders and expert for critiques and recommendations. Expert panels comprise of the academicians and stakeholders. Content validity was calculated by using the percentage of experts' agreement. Individuals can use this app to report inappropriate behaviour in a discreet and secure manner. Employees and employers can use this app to take action against WPV in the workplace in a simple, discreet, and quick manner. Its goal is to encourage employees to come forward and report WPV cases. It encourages both employees and management to unite together and change their own workplace cultures in order to put an end to WPV once and for all.